2020
DOI: 10.1371/journal.pntd.0008476
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of dengue and COVID-19: A case report

Abstract: Dengue and coronavirus disease 2019 (COVID-19) may share clinical and laboratory features. Reunion Island is a French overseas department located in the Indian Ocean with a population of more than 850,000 inhabitants. Due to its tropical climate, Reunion Island is at risk of arbovirus outbreaks. An increase in the number of dengue cases has been reported on the island since the beginning of 2018, with 3 different serotypes circulating mostly in austral summer. According to the last epidemiological report of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
2
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 11 publications
1
75
2
7
Order By: Relevance
“…Although, proposed by Verduyn et al (2020) [ 30 ] that early high IgM and IgG levels observed in SARS-CoV-2 infection may increase disease severity in the case of Dengue co-infection, this hypothesis did not find support in our data. As shown here, IgM index on Chikungunya and SARS-CoV-2 co-infection samples was significantly reduced (p<0.0001) when compared to Chikungunya infection alone ( Fig 7A ), and undistinguishable when Dengue and Dengue/SARS-CoV-2 were compared ( Fig 7B ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although, proposed by Verduyn et al (2020) [ 30 ] that early high IgM and IgG levels observed in SARS-CoV-2 infection may increase disease severity in the case of Dengue co-infection, this hypothesis did not find support in our data. As shown here, IgM index on Chikungunya and SARS-CoV-2 co-infection samples was significantly reduced (p<0.0001) when compared to Chikungunya infection alone ( Fig 7A ), and undistinguishable when Dengue and Dengue/SARS-CoV-2 were compared ( Fig 7B ).…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first confirmed case of co-infection of dengue and COVID-19 in Indonesia. Two clear cases of co-infection have been reported previously in Reunion Island ( Verduyn et al, 2020 ) and in Mayotte of French ( Epelboin et al, 2020 ). Nevertheless possible co-infection also have been noticed in Asia ( Miah and Husna, 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…[ 11 ] reported COVID-19 and dengue co-infection in a 40-year-old returning traveler and Verduyn et al . [ 12 ] published combination of these dual infections in an 18-year-old male adolescent. None of these two patients had severe manifestation.…”
Section: Discussionmentioning
confidence: 99%